Identification of the source events for aerosol generation during oesophago-gastro-duodenoscopy. Issue 5 (29th June 2021) - Gregson, Florence K A; Shrimpton, Andrew J; Hamilton, Fergus; Cook, Tim M; Reid, Jonathan P; Pickering, Anthony E; Pournaras, Dimitri J; Bzdek, Bryan R; Brown, Jules
Abstract : Objective: To determine if oesophago-gastro-duodenoscopy (OGD) generates increased levels of aerosol in conscious patients and identify the source events. Design: A prospective, environmental aerosol monitoring study, undertaken in an ultraclean environment, on patients undergoing OGD. Sampling was performed 20 cm away from the patient's mouth using an optical particle sizer. Aerosol levels during OGD were compared with tidal breathing and voluntary coughs within subject. Results: Patients undergoing bariatric surgical assessment were recruited (mean body mass index 44 and mean age 40 years, n=15). A low background particle concentration in theatres (3 L −1 ) enabled detection of aerosol generation by tidal breathing (mean particle concentration 118 L −1 ). Aerosol recording during OGD showed an average particle number concentration of 595 L −1 with a wide range (3–4320 L −1 ). Bioaerosol-generating events, namely, coughing or burping, were common. Coughing was evoked in 60% of the endoscopies, with a greater peak concentration and a greater total number of sampled particles than the patient's reference voluntary coughs (11 710 vs 2320 L −1 and 780 vs 191 particles, n=9 and p=0.008). Endoscopies with coughs generated a higher level of aerosol than tidal breathing, whereas those without coughs were not different to the background. Burps also generated increased aerosol concentration, similar to those recorded during voluntary coughs. The insertion and removal of the endoscope were not aerosol generating unless a cough was triggered. Conclusion: Coughing evoked during OGD is the main source of the increased aerosol levels, and therefore, OGD should be regarded as a procedure with high risk of producing respiratory aerosols. OGD should be conducted with airborne personal protective equipment and appropriate precautions in those patients who are at risk of having COVID-19 or other respiratory pathogens.